1988
DOI: 10.1177/106002808802201004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Administration of Two Standard Intravenous Amino Acid Formulas to Severely Brain-Injured Patients

Abstract: Twenty severely brain-injured patients with Glasgow Coma Scale scores of 4-9 were prospectively randomized to receive one of two standard amino acid formulas, starting with the first day of hospital admission up to day 14 postinjury. Formula 2 (patient group 2) had 54 percent more leucine, 53 percent more isoleucine, 74 percent more valine, 28 percent less phenylalanine, 31 percent less methionine, 111 percent more proline, 38 percent less alanine, and 38 percent less glycine than formula 1 (patient group 1). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 18 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…Only a few clinical studies have examined the consequences of amino acid supplementation after TBI. Ott et al ( 1988 ) compared the effects of two different intravenous amino acid formulations on amino acid levels and nitrogen balance in sTBI patients. Their results indicated that positive nitrogen balance could be achieved with early administration of some combinations of amino acids, although neither the specific amino acids responsible for this improvement, nor their effect on outcome was assessed (Ott et al, 1988 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few clinical studies have examined the consequences of amino acid supplementation after TBI. Ott et al ( 1988 ) compared the effects of two different intravenous amino acid formulations on amino acid levels and nitrogen balance in sTBI patients. Their results indicated that positive nitrogen balance could be achieved with early administration of some combinations of amino acids, although neither the specific amino acids responsible for this improvement, nor their effect on outcome was assessed (Ott et al, 1988 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ott et al ( 1988 ) compared the effects of two different intravenous amino acid formulations on amino acid levels and nitrogen balance in sTBI patients. Their results indicated that positive nitrogen balance could be achieved with early administration of some combinations of amino acids, although neither the specific amino acids responsible for this improvement, nor their effect on outcome was assessed (Ott et al, 1988 ). BCAAs play important roles in regulating protein synthesis, gluconeogenesis, and energy metabolism as well as functioning as a major source of nitrogen for producing glutamine and nitric oxide (Fernstrom, 2005 ; Jeter et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, methionine supplementation in TBI patients during the acute injury phase could potentially improve disease prognosis. Currently, only a few clinical studies are available assessing the potential benefits of intravenous methionine supplementation [ 48 , 49 , 50 ]. However, Dash et al, 2016 did not account for variability in plasma methionine concentrations due to food source, a potential limitation of the study.…”
Section: Discussionmentioning
confidence: 99%
“…214,215 Enriched parenteral and enteral feedings containing branched chain amino acids (BCAA) have been shown to improve nitrogen balance with decreased nitrogen excretion. 217,218 Effect on morbidity and mortality was not assessed in these studies. Relatively few studies have specifically addressed the impact of providing a high-protein (including BCAA) high-caloric intake on overall outcome in head-injured patients.…”
Section: Nutrition In Head-injured Patientsmentioning
confidence: 99%